2022
DOI: 10.3390/ani13010134
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Restoration Practices within a Semi-arid Natural Gas Field Improve Insect Abundance and Diversity during Early and Late Growing Season

Abstract: Insects are critical components of terrestrial ecosystems and are often considered ecosystem engineers. Due to the vast amount of ecosystem services they provide, because statistically valid samples can be captured in short durations, and because they respond rapidly to environmental change, insects have been used as indicators of restoration success and ecosystem functionality. In Wyoming (USA), ecological restoration required on thousands of acres of land surface have been disturbed to extract natural gas. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…While little statistically significant differences were found among vegetation cover class groups across this study, it may be important to note that grass, forb, and total vegetation cover had higher mean cover percentages in all study areas. As older stands of sagebrush found in the reference system of the Pinedale Anticline natural gas field have not shown to host large amounts of insect diversity ¬[46, 47], it is perhaps not surprising that insect abundance was significantly greater on well pad groups compared to reference sites in 3 of 5 areas with diversity at the species and family levels being significantly higher on reclaimed sites in 4 of 5 areas studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While little statistically significant differences were found among vegetation cover class groups across this study, it may be important to note that grass, forb, and total vegetation cover had higher mean cover percentages in all study areas. As older stands of sagebrush found in the reference system of the Pinedale Anticline natural gas field have not shown to host large amounts of insect diversity ¬[46, 47], it is perhaps not surprising that insect abundance was significantly greater on well pad groups compared to reference sites in 3 of 5 areas with diversity at the species and family levels being significantly higher on reclaimed sites in 4 of 5 areas studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, its findings are important as it is the first to examine how reclaimed well pads which are greater than 3-years-old compare to adjacent reference areas in a sagebrush-steppe ecosystem. Previous research in Sublette County natural gas fields clearly showed well pads undergoing reclamation which were 3-years-old and under had more insect abundance and diversity than old stands of reference area sagebrush [46, 47], which is consistent with successional theory suggesting biodiversity peaks in early successional stages [61]. While successional processes develop over long periods of time in cold, arid environments, knowing that reclaimed well pads from 5-12 years old are able to support enhanced biodiversity during peak growing season is encouraging as understanding biodiversity loss and ecosystem restoration have been considered 2 of the top 4 opportunities for future ecological successional studies [62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measuring insect richness and diversity has shown to be a sound indicator of ecosystem functionality and restoration success since insects respond rapidly to environmental change, provide more ecosystem services than other animals, and because statistically valid samples can be obtained in a short time period [42,43]. Efforts to understand insect response to restoration efforts are heavily focused on pollinators in crop agriculture ecosystems [44] and very few studies have been conducted to determine how insects respond to reclamation associated with oil and natural gas development [45][46][47]. Previous studies examining how insects respond to reclamation practices on Sublette County natural gas well pads show well pads exhibiting early successional vegetation (1-3 years post reclamation initiation) contain higher insect abundance and diversity than adjacent reference ecosystems [46,47].…”
Section: Introductionmentioning
confidence: 99%